N‒N Bond Lengths and the Initiation Reactivity (Sensitivity) of Nitramines - Zeman, Svatopluk; Atalar, Taner; Růžička, Aleš (My University, 2020)
On 16 selected nitramines, it is shown that an increase in the energy content of their molecules (represented by enthalpies of formation) is connected with an increase in the lengths of the longest N‒N bonds in their molecules. These lengths are directly proportional to the activation energies of the low-temperature thermal decomposition of pure nitramines in all states of matter of this reaction. Raising the energy content leads also to a reduction in the rate constants of thermal decomposition. Both of these facts are in contrast with expectations and also with similar published findings about the thermal decomposition of nitramines in solution, which can be explained by the solvation effect and termination of the emerging aza-radicals in solutions. The calculated dissociation energies of the weakest N‒N bonds yielded a relatively good reciprocal conformity with the lengths of the longest N‒N bonds of the nitramines studied, especially when using the UB3LYP/6-31G* method. The relationship between the impact sensitivity of the nitramines studied and the length of the longest N‒N bonds in their molecules is not completely clear. Such lengths cannot be a measure of impact sensitivity, because the longest N‒N bond might be stabilized by a suitable intermolecular interaction with the adjacent molecule in the crystal lattice
Délky N-N vazeb a iniciační reaktivita (citlivost) nitraminů.
Keywords: bond length; impact; nitramines; sensitivity; thermal decomposition; X-ray spectroscopy; délka vazby; náraz; nitraminy; citlivost; tepelný rozklad; rentgenová spektroskopie